Childhood after the jail: the drama of the children that grow in the prisons - Goicochea Elías, José Julio (2019)
Although it is important that the child is with his mother during the first years of his life, but this right as much as the mother as the child collides when the mother is serving a sentence,because the prisons do not have the infrastructure or the personnel to guarantee, protect, provide and cover the basic needs of the inmates themselves, much less those of a child as their, health, education, recreation, among others.This is where the participation and interest of the State as administrator in charge of safeguarding the rights of all citizens and protecting the Principle of the Higher Interest of the Child determines the decision of any person and the law, more favorable to safeguard and protected their interests.